Degradation of Indigo Dye Using Quantum Mechanical Calculations (Baghdad Science Journal, 2023)
The semiempirical (PM3) and DFT quantum mechanical methods were used to investigate the theoretical degradation of Indigo dye. The chemical reactivity of the Indigo dye was evaluated by comparing the potential energy stability of the mean bonds. Seven transition states were suggested and studied to estimate the actually starting step of the degradation reaction. The bond length and bond angle calculations indicate that the best active site in the Indigo dye molecule is at C10=C11.  The most possible transition states are examined for all suggested paths of Indigo dye degradation predicated on zero-point energy and imaginary frequency. The first starting step of the reaction mechanism is proposed. The change in enthalpy, Gibbs free energy and change in entropy of the overall reaction are equal to -548268.223 kcal/mol, 30831.951 kcal/mol and 48.552 cal/mol.deg, respectively. The activation energy is 46176.405 kcal/mol. The reaction rate is equal to .